Verifying the curriculum of a family medicine clerkship. - Snell LM; Battles JB; Bedford JA; Washington ET (Medical Education, 1998)
The learning experience during a medical school clinical rotation is largely shaped by students' patient encounters. This paper reports on how a log system for recording these encounters can be used for course planning and evaluation. Over the past 5 years, 960 third-year students completed log forms based on their clinical encounters during a required 4-week family medicine clerkship at UT Southwestern. These forms were then optically scanned and the information entered into a computerized database. Log form data revealed that the most common medical problems encountered by students in their ambulatory settings were similar to those reported in the general family practice literature. There was a great deal of consistency in the types of encounters from year to year. The data also showed some differences among clerkship sites in terms of patient demographics and the most frequently reported diagnoses. Information generated from student log forms has been used by the clerkship faculty to determine required readings, prioritize didactic topics and other teaching, adjust curriculum content, prepare support materials and develop examinations. Given the utility of the information obtained and the ease of use of optical mark encounter sheets, we recommend this system for other clerkships.